Gen Z's Financial Transformation: From Latte Factor to Stock Investment Through Capital Market Literacy - Nurhidayah; Ita Athia; Dwiyani Sudaryanti; Irma Hidayati; Dicky Pratama Putra; Niken Widya Ningrum; M. Bayu Rayhan; Erika Dwi Rahmawati (International Journal of Community Service Implementation, 2025)
This service contains activities regarding outreach regarding strategies for shifting funds from small and routine expenses, known as latte factors, to stock investments to Gen Z (AnNur-Bululawang High School students), as an effort to improve financial health, through strengthening capital market literacy. Gen Z has unique characteristics in financial management and investment preferences that are different compared to previous generations. Therefore, a special approach is required to optimize their financial potential. Latte factor refers to small expenses that are often considered trivial but can cumulatively hamper long-term savings and investment potential. Providing education with the aim of strengthening the capital market is the main key to increasing their knowledge about the capital market so that Gen Z can make more informed investment decisions and be able to manage their finances more wisely. The results of the activity provide the benefit of increasing knowledge about the negative impact of the latte factor habit and awareness about diverting latte factor funds into wiser financial decisions through stock investments